Uso de kefir na dieta líquida de bezerras(os) lactentes - Oliveira, Bruna Morais de (2021)
The rate of diarrhea in newborn calves is a problem in the development of the animal, mainly causing high mortality. In view of this problem, this study sought to evaluate the use of the probiotic Kefir in the calf lactation phase (0 to 60 days). The experiment was conducted Unidade de Ensino e Pesquisa Bovinocultura Leiteira localized Universidade Tecnológica Federal do Paraná, Campus Dois Vizinhos. Due to the pandemic it was not possible to carry out the evaluation with all the animals results. Five animals were taken, divided into three treatments: 1. Control animals, receiving only milk as a liquid diet; 2. Animals receive 30 g of kefir concentrate per day, reduced to milk three times a week and; 3. Animals receive 30 g of Kefir concentrate per day, reduced to milk five times a week. It is concluded that even with the limitations of work and the pandemic (COVID-19), the animals that consumed kefir 3 x week and 5 x week had a live weight of weaning, average daily gain after breastfeeding, consumption of dry matter larger powders and lactation than animals that did not consume kefir. Kefir aided maintenance during the period of diarrhea.